Pengaruh Literasi Keuangan Terhadap Pengelolaan Keuangan UMKM di Kota Makassar - Ardiansyah, A. Ferry Ardiansyah; Rauf, Anwar; Nurman, Nurman (CV. Lafadz Jaya, 2022)
This study aims to determine the effect of Financial Literacy on the financial management of Micro, Small and Medium Enterprises in Makassar City. The variables in this study are financial literacy as the independent variable (X) and financial management as the dependent variable (Y). The population in this study is all Micro, Small and Medium Enterprises in Makassar City which are registered with the Office of Cooperatives and Micro, Small and Medium Enterprises in Makassar City. Based on the data obtained, the number of Micro, Small and Medium Enterprises that are still active in 2021 in Makassar City is 715 Micro, Small and Medium Enterprises. The sampling technique used was the purposive sampling technique, namely the sample selection process using certain considerations. Data collection techniques used are questionnaires and documentation. The data analysis technique used is descriptive percentage analysis, instrument test, and hypothesis testing. The instrument test consists of a validity test and a reliability test. Hypothesis test consists of simple regression, partial test (t test) and partial determination coefficient (r2). The results of this study indicate that financial literacy partially has a positive and significant effect on the financial management of Micro, Small and Medium Enterprises in Makassar City.